[Student plays guitar in North Mountain Hall dorm] (1977)
Two students sitting inside a North Mountain room with one playing a nylon acoustic guitar while sitting on a bed and the other listening and sitting on an end table or vanity. A small Woodstock figurine from Charles Schulz' 'Peanuts' nearby. A kite and plants are hanging from the ceiling, with posters and framed images decorating the walls and a small tea set sitting on a low shelf nearby.